Profitability Review of Islamic Banks in Indonesia - Dahrani, Dahrani; Nainggolan, Edisah Putra (Journal of International Conference Proceedings, 2023)
This study aims to analyze the Profitability Review of Islamic Commercial Banks in Indonesia. Profitability is measured by the Return on Assets (ROA) indicator which is influenced by Mudharabah Financing and Musyarakah Financing. The population in this study is Islamic Commercial Banks in Indonesia, with a sample of 10 banks selected purposively. This study used a quantitative approach and the data were analyzed using multiple linear regression techniques. The results show that mudharabah financing partially has a positive and significant effect on profitability (ROA). Meanwhile, musyarakah financing partially has a negative and significant effect on profitability (ROA). Then mudharabah financing and musyarakah financing simultaneously affect profitability (ROA) in Islamic commercial banks in Indonesia